Inflation Forecast Targeting: The Swedish Experience - Claes Berg (Sveriges Riksbank, 2000)
In this paper key points in the development of the present Swedish inflation-targeting strategy are analysed. Since the implementation of the inflation target strategy began in 1993, three different phases are distinguished: the establishment of the inflation target, the communication of explicit inflation forecasts, and, finally, the introduction of distribution forecast targeting. In practice, distribution forecast targeting involves presenting a main scenario for future inflation, and assessments of both the degree of uncertainty in the forecast and the magnitude of the upside and downside risks in the main scenario in quarterly inflation reports. While inflation targeting in Sweden has been succesful in reducing both inflation and private sector inflation expectations, aggregate demand as well as supply shocks and temporary factors have also exerted a downward influence on inflation in the 1990s. It is therefore premature to distinguish any improvements in the inflation-output trade-off. It is likely, however, that the increased credibility of the inflation target has resulted in both a lower average inflation level and lower inflation variability.
Keywords: E50; 330; Inflation targeting; Distribution forecast targeting